Perceptions of Mexican women regarding barriers in mental Heath Services in primary care - Jorge Galván (BMC Women's Health, 2017)
Abstract Background The recent mental health care reforms in Mexico call for the regular evaluation of the services provided. This involves analyzing the opinions of those who utilize them on a daily basis, particularly women, since they are the main health service users. This study explores the barriers to mental health care perceived by a group of women attending primary care centers. Method A qualitative methodological approach was chosen. The participants were purposively selected, using the snowball technique. Semi-structured interviews were analyzed using the thematic analysis. Results Three sets of factors representing barriers to care were identified in the participants’ discourse. The first is linked to systemic barriers such as a lack of familiarity with the way the service operates, and irregularities in the consultations and appointment schedules that are not always geared to women’s needs. The second concerns the social stigma associated with emotional and/or mental disorders and their care while the third involves the characteristics of psychologists and their professional work. Conclusions In order to overcome some of the barriers identified, users should be given information on the work of mental health professionals, which would help dispel certain misconceptions and sensitize them to the importance of this type of treatment in achieving overall health. There is also a need to make psychologists aware of the living conditions and socio-cultural context of the women who attend these health facilities.